Distinguishing the Effects of Functional and Dysfunctional Conflict on Strategic Decision Making: Resolving a Paradox for Top Management Teams - Amason, Allen C. (Academy of Management Journal, 1996)
Top management teams make strategic decisions, and the products of their decision making influence organizational performance. However, a subtle paradox is embedded in this relationship. This study focuses on conflict as the crux of this paradox and provides evidence from two different samples of conflict's consistent yet contradictory effects on decision quality, consensus, and affective acceptance.